Current collector and preparation method thereof, pole piece and secondary battery
By performing multi-stage electroplating and anti-oxidation treatment on the base film of the composite fluid collector, the contact angle of the current collector surface is reduced, the problem of insufficient adhesion of the current collector in the prior art is solved, and the circulation performance of the battery is improved.
Patent Information
- Application Number
- CN202411598470.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The contact angle of the conductor layer of the existing composite fluid collector is large, resulting in hydrophobic areas during the coating process of the negative electrode slurry, insufficient peeling strength, and poor battery circulation performance.
By depositing a metal layer on the base film and adopting at least two stages of electroplating, including fine crystal strengthening stage electroplating, combined with anti-oxidation treatment, the contact angle of the current collector surface is reduced and the adhesion to the active material layer is increased.
The contact angle of the current collector surface is reduced, the adhesion to the active material layer is enhanced, and the conductivity and battery cycling performance are improved.
Smart Images

Figure CN119601666A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a current collector and a preparation method thereof, a pole piece, and a secondary battery. Background Art
[0002] Lithium batteries are used as power batteries for new energy vehicles and batteries for 3C digital products due to their high energy density, high output power and long cycle life.
[0003] In recent years, with the popularity of new energy vehicles, lithium batteries have also attracted widespread attention. However, more and more safety accidents caused by lithium battery combustion and explosion have forced people to pay attention to their safety performance. Most combustion and explosion are caused by short circuit in the battery. The battery core discharges with a large current, generates a lot of heat, burns the diaphragm, and causes a larger short circuit. In this way, the battery core will generate high temperature, decompose the electrolyte into gas, and cause excessive internal pressure. When the shell of the battery core cannot withstand this pressure, the battery core will explode.
[0004] Someone has proposed a new composite current collector with a structure of conductor layer-polymer layer-conductor layer. The metal layer is used to carry the electrode active material layer. This structure has the following characteristics: 1. During the temperature rise stage caused by overshoot and short circuit, the plastic insulating layer melts or swells, and the metal layer (copper) becomes discontinuous, so the resistance increases rapidly and the current decreases rapidly, suppressing the generation of Joule heat. 2. The thickness of the metal layer is reduced (6 to 2 microns), which reduces the probability of burrs on the metal layer and reduces the risk of short circuit. Therefore, the new current collector with this structure can effectively reduce the local temperature surge caused by short circuit in the battery and reduce the risk of fire and explosion of lithium-ion batteries.
[0005] At present, composite current collectors are all made by depositing a metal layer on the polymer layer by sputtering to metallize the polymer surface, and then thickening the metal layer through a single electroplating and anti-oxidation process. However, the conductor layer of the composite current collector has a large contact angle (80°~110°), and hydrophobic areas appear during the coating process of the negative electrode slurry; after coating, the pole piece peeling strength is insufficient, and the battery cycle performance is poor. Summary of the invention
[0006] The present application provides a current collector and a preparation method thereof, a pole piece, and a secondary battery, so that the surface of the current collector has a lower contact angle, thereby increasing its adhesion to the active material layer when used as a pole piece.
[0007] In a first aspect, an embodiment of the present application provides a current collector, comprising a base film and a metal layer attached to the surface of the base film, the surface contact angle of the current collector is 60° to 80°, and the square resistance of the current collector is 2 to 200 mΩ / □.
[0008] In the above implementation process, the current collector has a lower surface contact angle, and when used as a pole piece, it can have greater adhesion with the active material layer. At the same time, the current collector has a lower square resistance, so that it has better conductivity and can adapt to high current conditions.
[0009] As an optional embodiment, the base film material of the current collector includes at least one of polyethylene, biaxially oriented polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate and polypropylene; and / or
[0010] The base film thickness of the current collector is 2 μm to 20 μm; and / or
[0011] The thickness of the metal layer of the current collector is 0.1 μm to 10 μm.
[0012] In the above implementation process, by using a suitable material as the base film and / or selecting a suitable base film thickness and / or selecting a suitable metal layer thickness, the current collector has better comprehensive performance.
[0013] In a second aspect, an embodiment of the present application provides a method for preparing a current collector, the method comprising:
[0014] A surface metallized base film is obtained;
[0015] Electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0016] Performing an anti-oxidation treatment on the primary current collector to form an anti-oxidation layer to obtain a current collector;
[0017] The electroplating process includes at least two stages of electroplating, and the last stage of electroplating in the electroplating process is a grain refinement strengthening stage of electroplating.
[0018] In the above implementation process, by adopting an electroplating treatment process with at least two stages of electroplating, and controlling the last stage of electroplating to be a fine grain strengthening stage of electroplating, and combining it with anti-oxidation treatment, the contact angle of the collector surface is reduced, and its hydrophilicity is improved, thereby increasing its adhesion to the active material layer when used as a pole piece.
[0019] As an optional implementation, the electroplating process in the grain refinement strengthening stage meets the following requirements: electroplating time is 5s to 30s, electroplating current density is 0.2ASD to 1ASD, and electroplating temperature is 20°C to 30°C.
[0020] In the above implementation process, by selecting appropriate electroplating process parameters in the fine grain strengthening stage, it is more conducive to reducing the contact angle of the current collector surface, thereby increasing its adhesion to the active material layer when used as a pole piece.
[0021] As an optional implementation, the electroplating process includes four stages of electroplating.
[0022] As an optional implementation, the first stage of the four-stage electroplating is current ramp stage electroplating, and the process of the current ramp stage electroplating meets the following requirements: electroplating time is 0.5min to 1min, electroplating current density is 0.2ASD to 1ASD, and electroplating temperature is 30°C to 50°C.
[0023] In the above implementation process, by controlling the process parameters of electroplating in the current ramping stage, the current density of electroplating in the current ramping stage is made smaller, which can avoid the base metal from falling off due to excessive current.
[0024] As an optional implementation, the second stage of the four-stage electroplating is a stable continuous stage electroplating, and the process of the stable continuous stage electroplating meets the following requirements: electroplating time is 1min to 3min, electroplating current density is 1ASD to 3ASD, and electroplating temperature is 20°C to 50°C.
[0025] In the above implementation process, by controlling the process parameters of the electroplating in the stable continuous stage, the metal layer generated by the electroplating in the stable continuous stage has low square resistance and good conductivity, and can adapt to high current conditions.
[0026] As an optional implementation, the third stage of the four-stage electroplating is grain coarsening stage electroplating, and the process of the grain coarsening stage electroplating meets the following requirements: electroplating time is 10s to 20s, electroplating current density is 2.5ASD to 3ASD, and electroplating temperature is 50°C to 60°C.
[0027] In the above implementation process, by controlling the process parameters of electroplating in the grain coarsening stage, the metal particles of the metal layer electroplated in the grain coarsening stage are larger, which is more conducive to the conductivity and mechanical properties of the current collector.
[0028] As an optional implementation, the electroplating process includes: electroplating in a current ramping stage, electroplating in a stable continuous stage, electroplating in a grain coarsening stage, and electroplating in a grain refinement strengthening stage;
[0029] The components of the plating solution in the current ramping stage electroplating, the stable continuous stage electroplating and the fine grain strengthening stage electroplating satisfy any one of the following (A) to (F):
[0030] (A) The mass concentration of CuSO4·5H2O is 100g / L~300g / L;
[0031] (B) The mass concentration of H2SO4 is 20g / L to 90g / L;
[0032] (C)Cl - The mass concentration is 10mg / L~100mg / L;
[0033] (D) the mass concentration of tetrahydrothiazolidinethione is 0.0005 g / L to 0.001 g / L;
[0034] (E) the mass concentration of sodium poly(2,6-bis(2,6-propane sulfonate)) is 0.01 g / L to 0.02 g / L;
[0035] (F) the mass concentration of polyethylene glycol is 0.03 g / L to 0.05 g / L;
[0036] Wherein, the components of the electroplating solution in the grain coarsening stage satisfy any one of the following (G) to (J):
[0037] (G) The mass concentration of CuSO4·5H2O is 30 g / L to 100 g / L;
[0038] (H) The mass concentration of H2SO4 is 20g / L~90g / L;
[0039] (I) The mass concentration of glucose is 15 g / L to 25 g / L;
[0040] (J) The mass concentration of ammonium molybdate is 10 g / L to 20 g / L.
[0041] In the above implementation process, by controlling the composition of the plating solution at each stage, the metal layer can be better deposited, so that the current collector has better performance. For example, in the plating solution of the grain coarsening stage, the use of low metal ion concentration combined with high current density is more conducive to the formation of large particles of metal.
[0042] As an optional embodiment, the anti-oxidation treatment comprises immersing the primary current collector in an anti-oxidation liquid, wherein the anti-oxidation liquid comprises a BTA corrosion inhibitor and ammonium molybdate.
[0043] In the above implementation process, the anti-oxidation liquid is formed by combining BTA corrosion inhibitor and ammonium molybdate, which can further reduce the contact angle of the current collector surface, thereby increasing the adhesion between the current collector and the active material layer when used as a pole piece.
[0044] As an optional embodiment, the mass concentration of the BTA corrosion inhibitor in the anti-oxidation solution is 5 mg / L to 60 mg / L; and / or
[0045] The mass concentration of ammonium molybdate in the anti-oxidation liquid is 5 mg / L to 80 mg / L; and / or
[0046] The soaking time is 2 to 5 minutes; and / or
[0047] The soaking temperature is 30°C to 70°C.
[0048] In the above implementation process, by controlling the process parameters during the immersion process, the anti-oxidation treatment can be better achieved, which is beneficial to the anti-oxidation performance of the current collector.
[0049] In a third aspect, an embodiment of the present application provides a pole piece, which includes the current collector provided in the first aspect or the current collector produced by the method provided in the second aspect.
[0050] In a fourth aspect, an embodiment of the present application provides a secondary battery, wherein the secondary battery includes the electrode provided in the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0052] Figure 1 A schematic diagram of the structure of the current collector provided in an embodiment of the present application;
[0053] Figure 2 A flowchart of a method provided in an embodiment of the present application;
[0054] Figure 3 A schematic diagram of the structure of the pole piece provided in an embodiment of the present application.
[0055] Reference numerals: 1 - current collector; 11 - base film; 12 - metal layer; 2 - active material layer. DETAILED DESCRIPTION
[0056] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0057] At present, composite current collectors are all made by depositing a metal layer on the polymer layer by sputtering to metallize the polymer surface, and then thickening the metal layer through a single electroplating and anti-oxidation process. However, the conductor layer of the composite current collector has a large contact angle (80°~110°), and hydrophobic areas appear during the coating process of the negative electrode slurry; after coating, the pole piece peeling strength is insufficient, and the battery cycle performance is poor.
[0058] The present application intends to provide a current collector, the surface of which has a lower contact angle, thereby increasing its adhesion to the active material layer when used as a pole piece.
[0059] Figure 1 A schematic diagram of the structure of the current collector provided in the embodiment of the present application, such as Figure 1 As shown, an embodiment of the present application provides a current collector, the current collector 1 includes a base film 11 and a metal layer 12 , and in the thickness direction of the base film 11 , both sides of the base film 11 are directly connected to the metal layer 12 .
[0060] It should be noted that the thickness of the base film is not limited and can be adjusted according to actual needs.
[0061] As an example, the thickness of the base film is 2 μm to 20 μm, for example but not limited to any one of 2 μm, 5 μm, 10 μm, 15 μm and 20 μm or a range between any two of the thicknesses.
[0062] In this embodiment, limiting the thickness of the base film within a specific range can make the base film have a suitable thickness, thereby making the base film have suitable mechanical properties and electrochemical properties.
[0063] It should be noted that the thickness of a single metal layer is not limited and can be adjusted according to actual needs.
[0064] As an example, the thickness of a single metal layer is 0.1 μm to 10 μm, for example but not limited to any one of 0.1 μm, 2 μm, 4 μm, 6 μm, 8 μm and 10 μm or a range between any two of the thicknesses.
[0065] In this embodiment, the thickness of a single metal layer is limited to a specific range, so that the single metal layer can have a suitable thickness, thereby ensuring the conductivity while taking into account a lower preparation cost.
[0066] It should be noted that the sheet resistance of a single metal layer is not limited and can be adjusted according to actual needs.
[0067] Sheet resistance (i.e., square resistance) refers to the edge-to-edge resistance of a square thin film conductive material. Sheet resistance is defined as: Sheet resistance R = ρ / d, where ρ is the resistivity of the material and d is the thickness of the material.
[0068] As an example, the square resistance of a single metal layer is 2 to 200 mΩ / □, for example but not limited to any point value among 2 mΩ / □, 50 mΩ / □, 100 mΩ / □, 150 mΩ / □ and 200 mΩ / □, or a range value between any two of them.
[0069] In this embodiment, the thickness of a single metal layer is limited to a specific range, so that the single metal layer has a suitable square resistance and thus has a suitable conductivity. For example, the thickness of the metal layer of the current collector is 0.1 μm to 10 μm, and the corresponding metal layer square resistance is 2 to 200 mΩ.
[0070] It should be noted that the surface contact angle of the current collector is not limited and can be adjusted according to actual needs.
[0071] As an example, the surface contact angle of the current collector is 60° to 80°, for example but not limited to, the surface contact angle is any point value among 60°, 65°, 70°, 75° and 80° or a range value between any two thereof.
[0072] In this embodiment, the surface contact angle of the current collector is limited to a specific range, so that the surface of the current collector has a suitable contact angle, thereby enabling it to have a suitable binding force with the active material layer.
[0073] It is understandable that the relative positions of the two metal layers can be adjusted in consideration of the regularity of the current collector and the ease of preparation.
[0074] As an example, in the thickness direction of the base film, the orthographic projections of the two metal layers completely overlap.
[0075] In this embodiment, the orthographic projections of the two metal layers in the thickness direction of the base film completely overlap, that is, the two metal layers are distributed along the thickness direction of the base film and are symmetrical about the base film, so that the overall structure of the current collector is relatively regular and also facilitates process preparation.
[0076] In other possible implementations, in the thickness direction of the base film, the orthographic projections of the two metal layers may also partially overlap, that is, one metal layer is longer and the other metal layer is shorter.
[0077] Figure 2 For a flowchart of the method provided in the embodiment of the present application, please refer to Figure 2 Based on a general inventive concept, an embodiment of the present application also provides a method for preparing the current collector provided above.
[0078] This method is used to prepare the above-mentioned current collector. The specific content of the current collector can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.
[0079] In some embodiments, the method comprises:
[0080] S1. Obtaining a surface metallized base film;
[0081] It should be noted that the “base film with metallized surface” herein means that it can be obtained by direct purchase or prepared according to conventional processes in the art.
[0082] For example, a specific process for obtaining a surface metallized base film may be to deposit metal on both sides of the base film to obtain the surface metallized base film.
[0083] It should be noted that the specific method of metal deposition is not limited and can be performed according to conventional methods in the art.
[0084] As an example, in the step of depositing metal, at least one of physical vapor deposition and chemical plating is adopted; wherein physical vapor deposition includes at least one of vacuum evaporation, magnetron sputtering and ion beam evaporation coating.
[0085] It should be noted that the specific process of chemical plating treatment and the components and ratios of the corresponding reagents used are not limited and can be set according to conventional selections in the art.
[0086] As an example, in the process of chemical plating, the plating solution includes CuSO4, complexing agent-triethanolamine, Na2CO3, potassium sodium tartrate, thiourea, NaOH and formaldehyde; wherein the concentration of CuSO4 is 5-7g / L, the concentration of complexing agent-triethanolamine is 8-10mg / L, the concentration of Na2CO3 is 8-10mg / L, the concentration of potassium sodium tartrate is 70-75g / L, the concentration of thiourea is 0.005-0.01g / L, the concentration of formaldehyde is 8-10mg / L, NaOH is used as a pH regulator until the pH of the solution is 12, the treatment temperature is 40-50°C, and the treatment time is 10-30min.
[0087] It should be noted that based on different metal deposition processes, the preparation process can be adjusted accordingly taking into account the effect of metal deposition.
[0088] As an example, before the step of depositing metal by chemical plating, the base film is subjected to roughening, sensitization and activation treatments in sequence.
[0089] It should be noted that the specific processes of roughening, sensitization and activation treatments and the components and ratios of the corresponding reagents used are not limited and can be set according to conventional selections in the art.
[0090] As an example, during the roughening treatment, the roughening liquid includes sulfuric acid, water and chromic acid; wherein the volume ratio of sulfuric acid to water in the roughening liquid is 4:6, chromic acid is added as a component until the mixed solution is saturated, the treatment temperature is 60-70°C, and the treatment time is 20-30 minutes.
[0091] As an example, during the sensitization process, the sensitizing solution includes SnCl and HCl; wherein the concentration of SnCl is 0.05-0.1 g / L, the concentration of HCl is 0.2-0.4 g / L, and the treatment time is 2-4 min.
[0092] As an example, during the activation treatment, the activation solution includes AgNO3 and ammonia water; wherein the concentration of AgNO3 is 3 to 5 g / L, ammonia water is added as a component until the solution becomes transparent, and the treatment time is 5 to 10 minutes.
[0093] It is understandable that, since different types of metals have different physical and chemical properties, the optimal deposition process can be selected or adjusted according to actual needs in consideration of the effect of metal deposition.
[0094] As an example, the metal is Al. In the step of metal deposition, a vacuum evaporation method in a physical vapor deposition method is used to deposit metal Al on the surface of the base film to form a metal layer; wherein the vacuum degree is 1.3×10 -4 ~1.3×10 -2 Within the Pa range, the processing temperature is 500~2500℃.
[0095] It is understandable that since the evaporation temperature affects the density of the metal layer, the better the density, the stronger the bonding between the metal layer and the base film. Considering the bonding strength between the formed metal layer and the base film, the evaporation temperature can be further limited.
[0096] As an example, the metal is Cu, and after the step of depositing the metal is completed and before the step of removing the portion of the base film corresponding to the edge area of the metal layer, the step further includes thickening the metal layer.
[0097] S2. electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0098] In some embodiments, the electroplating process includes at least two stages of electroplating. Further, the electroplating process includes four stages of electroplating.
[0099] The first stage of the four-stage electroplating is a current ramp stage electroplating, wherein the mass concentration of CuSO4·5H2O in the electroplating solution of the current ramp stage electroplating is 100g / L to 300g / L, the mass concentration of H2SO4 is 20g / L to 90g / L, and the mass concentration of Cl - The mass concentration of is 10mg / L~100mg / L, the mass concentration of tetrahydrothiazolidinethione is 0.0005g / L~0.001g / L, the mass concentration of poly(dihexadimethoxypropane)sulfonate is 0.01g / L~0.02g / L, and the mass concentration of polyethylene glycol (such as PEG-6000) is 0.03g / L~0.05g / L. The electroplating process in the current ramp stage meets the following requirements: the electroplating time is 0.5min~1min, the electroplating current density is 0.2ASD~1ASD, and the electroplating temperature is 30℃~50℃. The current density in this stage is relatively small, which can avoid the base metal from falling off due to excessive current.
[0100] As an example, the mass concentration of CuSO4·5H2O is any one of 100 g / L, 150 g / L, 200 g / L, 250 g / L and 300 g / L or a range between any two of them. The mass concentration of H2SO4 is any one of 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L and 90 g / L or a range between any two of them. - The mass concentration of is 10g / L, 20g / L, 30g / L, 40g / L, 50g / L, 60g / L, 70g / L, 80g / L, 90g / L and 100g / L, or any range between two of them. The mass concentration of tetrahydrothiazolidinethione is 0.0005g / L, 0.0006g / L, 0.0007g / L, 0.0008g / L, 0.0009g / L and 0.001g / L, or any range between two of them. The mass concentration of sodium polydihexadimethoxypropane sulfonate is 0.01g / L, 0.015g / L and 0.02g / L, or any range between two of them. The mass concentration of polyethylene glycol (e.g., PEG-6000) is any one of 0.03 g / L, 0.04 g / L, and 0.05 g / L, or a range between any two of them. The electroplating time is any one of 0.5 min, 0.6 min, 0.7 min, 0.8 min, 0.9 min, and 1 min, or a range between any two of them. The electroplating current density is any one of 0.2 ASD, 0.4 ASD, 0.6 ASD, 0.8 ASD, and 1 ASD, or a range between any two of them. The electroplating temperature is any one of 30° C., 40° C., and 50° C., or a range between any two of them.
[0101] The second electroplating stage of the four-stage electroplating is a stable continuous stage electroplating, wherein the mass concentration of CuSO4·5H2O in the electroplating solution of the stable continuous stage electroplating is 100g / L to 300g / L, the mass concentration of H2SO4 is 20g / L to 90g / L, and the mass concentration of Cl - The mass concentration of is 10mg / L~100mg / L, the mass concentration of tetrahydrothiazolidinethione is 0.0005g / L~0.001g / L, the mass concentration of poly(262-propanesulfonate) is 0.01g / L~0.02g / L, and the mass concentration of polyethylene glycol (such as PEG-6000) is 0.03g / L~0.05g / L. The process of the stable continuous stage electroplating meets the following requirements: the electroplating time is 1min~3min, the electroplating current density is 1ASD~3ASD, and the electroplating temperature is 20℃~50℃. The metal layer formed in this stage has low square resistance and good conductivity, so it can adapt to high current working conditions.
[0102] As an example, the mass concentration of CuSO4·5H2O is any one of 100 g / L, 150 g / L, 200 g / L, 250 g / L and 300 g / L or a range between any two of them. The mass concentration of H2SO4 is any one of 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L and 90 g / L or a range between any two of them. - The mass concentration of is 10g / L, 20g / L, 30g / L, 40g / L, 50g / L, 60g / L, 70g / L, 80g / L, 90g / L and 100g / L, or any range between two of them. The mass concentration of tetrahydrothiazolidinethione is 0.0005g / L, 0.0006g / L, 0.0007g / L, 0.0008g / L, 0.0009g / L and 0.001g / L, or any range between two of them. The mass concentration of sodium polydihexadimethoxypropane sulfonate is 0.01g / L, 0.015g / L and 0.02g / L, or any range between two of them. The mass concentration of polyethylene glycol (eg, PEG-6000) is any one of 0.03 g / L, 0.04 g / L, and 0.05 g / L, or a range between any two of them.
[0103] The third stage of the four-stage electroplating is the grain coarsening stage electroplating. The mass concentration of CuSO4·5H2O in the electroplating solution of the grain coarsening stage electroplating is 30g / L-100g / L, the mass concentration of H2SO4 is 20g / L-90g / L, the mass concentration of glucose is 15g / L-25g / L, and the mass concentration of ammonium molybdate is 10g / L-20g / L. The electroplating process of the grain coarsening stage meets the following requirements: the electroplating time is 10s-20s, the electroplating current density is 2.5ASD-3ASD, and the electroplating temperature is 50℃-60℃. Low Cu is used in this stage. 2+ concentration, high current density, thereby reducing a large Cu particle layer at the cathode.
[0104] As an example, the mass concentration of CuSO4·5H2O is any one of 30g / L, 50g / L, 70g / L, 90g / L and 100g / L or a range between any two of them. The mass concentration of H2SO4 is any one of 20g / L, 30g / L, 40g / L, 50g / L, 60g / L, 70g / L, 80g / L and 90g / L or a range between any two of them. The mass concentration of glucose is any one of 15g / L, 16g / L, 17g / L, 18g / L, 19g / L, 20g / L, 21g / L, 22g / L, 23g / L, 24g / L and 25g / L or a range between any two of them. The mass concentration of ammonium molybdate is any one of 10g / L, 15g / L and 20g / L or a range between any two of them. The electroplating time is any one of 10s, 15s and 20s or a range between any two of them. The electroplating current density is any one of 2.5ASD, 2.6ASD, 2.7ASD, 2.8ASD, 2.9ASD and 3ASD or a range between any two of them. The electroplating temperature is any one of 50°C, 55°C and 60°C or a range between any two of them.
[0105] The fourth electroplating stage of the four-stage electroplating is a fine grain strengthening stage electroplating, wherein the mass concentration of CuSO4·5H2O in the electroplating solution of the fine grain strengthening stage electroplating is 100g / L to 300g / L, the mass concentration of H2SO4 is 20g / L to 90g / L, and the mass concentration of Cl -The mass concentration of is 10mg / L~100mg / L, the mass concentration of tetrahydrothiazolidinethione is 0.0005g / L~0.001g / L, the mass concentration of poly(262-propanesulfonate) is 0.01g / L~0.02g / L, and the mass concentration of polyethylene glycol (such as PEG-6000) is 0.03g / L~0.05g / L. The electroplating process in the fine grain strengthening stage meets the following requirements: the electroplating time is 5s~30s, the electroplating current density is 0.2ASD~1ASD, and the electroplating temperature is 20℃~30℃. This stage uses a small current to continue to deposit a finer copper layer on the large copper layer to prevent the large copper particles from falling off.
[0106] As an example, the mass concentration of CuSO4·5H2O is any one of 100 g / L, 150 g / L, 200 g / L, 250 g / L and 300 g / L or a range between any two of them. The mass concentration of H2SO4 is any one of 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L and 90 g / L or a range between any two of them. - The mass concentration of is 10g / L, 20g / L, 30g / L, 40g / L, 50g / L, 60g / L, 70g / L, 80g / L, 90g / L and 100g / L, or any range between two of them. The mass concentration of tetrahydrothiazolidinethione is 0.0005g / L, 0.0006g / L, 0.0007g / L, 0.0008g / L, 0.0009g / L and 0.001g / L, or any range between two of them. The mass concentration of sodium polydihexadimethoxypropane sulfonate is 0.01g / L, 0.015g / L and 0.02g / L, or any range between two of them. The mass concentration of polyethylene glycol (e.g., PEG-6000) is any one of 0.03 g / L, 0.04 g / L, and 0.05 g / L, or a range between any two of them. The electroplating time is any one of 5 s, 10 s, 15 s, 20 s, 25 s, and 30 s, or a range between any two of them. The electroplating current density is any one of 0.2 ASD, 0.4 ASD, 0.6 ASD, 0.8 ASD, and 1 ASD, or a range between any two of them. The electroplating temperature is any one of 20° C., 25° C., and 30° C., or a range between any two of them.
[0107] S3. Performing an anti-oxidation treatment on the initial current collector to form an anti-oxidation layer to obtain a current collector.
[0108] In some embodiments, the anti-oxidation treatment includes immersing the primary current collector in an anti-oxidation solution, wherein the anti-oxidation solution includes a BTA corrosion inhibitor and ammonium molybdate. By using a BTA corrosion inhibitor and ammonium molybdate to form an anti-oxidation solution, the contact angle of the current collector surface can be further reduced, thereby increasing the adhesion of the current collector to the active material layer when used as a pole piece.
[0109] Furthermore, the mass concentration of BTA corrosion inhibitor in the anti-oxidation solution is 5 mg / L to 60 mg / L, and the mass concentration of ammonium molybdate is 5 mg / L to 80 mg / L; the immersion time is 2 min to 5 min; and the immersion temperature is 30° C. to 70° C. By controlling the process parameters during the immersion process, the anti-oxidation treatment can be better achieved, which is beneficial to the anti-oxidation performance of the current collector.
[0110] As an example, the mass concentration of BTA corrosion inhibitor is any one of 5 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L and 60 mg / L or a range between any two of them. The mass concentration of ammonium molybdate is any one of 5 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L and 80 mg / L or a range between any two of them. The soaking time is any one of 2 min, 3 min, 4 min and 5 min or a range between any two of them; the soaking temperature is any one of 30°C, 40°C, 50°C, 60°C and 70°C or a range between any two of them.
[0111] Figure 3 A schematic diagram of the structure of the pole piece provided in the embodiment of the present application, such as Figure 3 As shown, based on a general inventive concept, an embodiment of the present application further provides a pole piece, which includes a current collector as provided above.
[0112] The pole piece is realized based on the above-mentioned current collector. The specific content of the current collector can refer to the above-mentioned embodiment. Since the pole piece adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0113] It should be noted that the specific type of the pole piece is not limited and can be adjusted according to the type of the current collector.
[0114] Exemplarily, the current collector is a positive electrode current collector, and the pole piece is a positive electrode pole piece; the current collector is a negative electrode current collector, and the pole piece is a negative electrode pole piece.
[0115] The secondary battery formed by the pole piece can be applied to various electrical devices, such as mobile phones, portable devices, laptop computers, battery vehicles, electric vehicles, ships, spacecraft, electric toys, energy storage devices and electric tools.
[0116] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0117] Example 1
[0118] A composite current collector, the preparation process of which is as follows:
[0119] S1. Obtaining a surface metallized base film;
[0120] S2. electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0121] S3. Performing an anti-oxidation treatment on the initial current collector to form an anti-oxidation layer to obtain a current collector.
[0122] The process of electroplating is:
[0123] ① In the first stage, a small current is used to cover the dense and fine copper layer on the metallized base film, and the thickness is appropriately increased to reduce its square resistance. The current density is 0.5ASD, and the electroplating time is 1min. The plating solution formula is: CuSO4·5H2O concentration is 200g / L, H2SO4 concentration is 50g / L, and the inorganic additive is Cl - , the concentration is 20mg / L, the organic additives include thiazolidinethione concentration of 0.001g / L, poly(2,6-bis-propane sulfonate) sodium concentration of 0.015g / L, and PEG-6000 concentration of 0.04g. The electroplating temperature is room temperature 25°C, and the plating solution is stirred continuously during the electroplating process to reduce concentration polarization;
[0124] ② In the second stage, a high current is used to further thicken the plating layer and further improve the copper plating efficiency. After the thickening treatment in the first stage, the square resistance of the metallization layer is reduced, so it can currently adapt to high current conditions. The plating solution formula in this stage is consistent with the formula in the first stage, and the current density is increased to 2ASD.
[0125] ③ In the third stage, a large-grain copper layer is grown on the copper-plated layer by adjusting the electroplating solution formula and current density. The formula for this stage is: CuSO4·5H2O concentration is 60g / L, H2SO4 concentration is 80g / L, glucose concentration is 18g / L, and ammonium molybdate concentration is 16g / L. The electroplating time is 15s, the current density is increased to 3ASD, and the temperature is heated to 45°C by a heating rod. Stirring is continued during the electroplating process.
[0126] ④The fourth stage uses a small current to deposit a thin copper layer to fix the large copper layer in the third step to prevent it from falling off. The formula of this stage is the same as the electroplating formula of the first stage. The refinement process is: electroplating time is 30s, current density is 0.2ASD, and temperature is 25℃.
[0127] The process of anti-oxidation treatment is:
[0128] The metal film after continuous electroplating is immersed in the prepared corrosion inhibition solution for 2 minutes, and the temperature of the corrosion inhibition solution is 45° C. The formula of this slow-release solution is: BTA concentration is 12 mg / L, and ammonium molybdate concentration is 15 mg / L.
[0129] Example 2
[0130] A composite current collector, the preparation process of which is as follows:
[0131] S1. Obtaining a surface metallized base film;
[0132] S2. electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0133] S3. Performing an anti-oxidation treatment on the initial current collector to form an anti-oxidation layer to obtain a current collector.
[0134] The process of electroplating is:
[0135] ① In the first stage, a small current is used to cover the dense and fine copper layer on the metallized base film, and the thickness is appropriately increased to reduce its square resistance. The current density is 0.5ASD, and the electroplating time is 1min. The plating solution formula is: CuSO4·5H2O concentration is 200g / L, H2SO4 concentration is 50g / L, and the inorganic additive is Cl - , the concentration is 20mg / L, the organic additives include thiazolidinethione concentration of 0.001g / L, poly(2,6-bis-propane sulfonate) sodium concentration of 0.015g / L, and PEG-6000 concentration of 0.04g. The electroplating temperature is room temperature 25°C, and the plating solution is stirred continuously during the electroplating process to reduce concentration polarization;
[0136] ② In the second stage, a high current is used to further thicken the plating layer and further improve the copper plating efficiency. After the thickening treatment in the first stage, the square resistance of the metallization layer is reduced, so it can currently adapt to high current conditions. The plating solution formula in this stage is consistent with the formula in the first stage, and the current density is increased to 2ASD.
[0137] ③ In the third stage, a large-grain copper layer is grown on the copper-plated layer by adjusting the electroplating solution formula and current density. The formula for this stage is: CuSO4·5H2O concentration is 60g / L, H2SO4 concentration is 80g / L, glucose concentration is 18g / L, and ammonium molybdate concentration is 16g / L. The electroplating time is 15s, the current density is increased to 3ASD, and the temperature is heated to 45°C by a heating rod. Stirring is continued during the electroplating process.
[0138] ④The fourth stage uses a small current to deposit a thin copper layer to fix the large copper layer in the third step to prevent it from falling off. The formula of this stage is the same as the electroplating formula of the first stage. The refinement process is: electroplating time is 30s, current density is 0.2ASD, and temperature is 25℃.
[0139] The process of anti-oxidation treatment is:
[0140] The metal film after continuous electroplating is immersed in the prepared corrosion inhibition solution for 2 minutes, and the temperature of the corrosion inhibition solution is 45° C. The formula of this slow-release solution is: BTA concentration is 15 mg / L.
[0141] Example 3
[0142] A composite current collector, the preparation process of which is as follows:
[0143] S1. Obtaining a surface metallized base film;
[0144] S2. electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0145] S3. The primary current collector is subjected to a roughening treatment, and then subjected to an anti-oxidation treatment to form an anti-oxidation layer to obtain a current collector.
[0146] The process of electroplating is:
[0147] ① In the first stage, a small current is used to cover the dense and fine copper layer on the metallized base film, and the thickness is appropriately increased to reduce its square resistance. The current density is 0.5ASD, and the electroplating time is 1min. The plating solution formula is: CuSO4·5H2O concentration is 200g / L, H2SO4 concentration is 50g / L, and the inorganic additive is Cl -, the concentration is 20mg / L, the organic additives include thiazolidinethione concentration of 0.001g / L, poly(2,6-bis-propane sulfonate) sodium concentration of 0.015g / L, and PEG-6000 concentration of 0.04g. The electroplating temperature is room temperature 25°C, and the plating solution is stirred continuously during the electroplating process to reduce concentration polarization;
[0148] ② In the second stage, a high current is used to further thicken the plating layer and further improve the copper plating efficiency. After the thickening treatment in the first stage, the square resistance of the metallization layer is reduced, so it can currently adapt to high current conditions. The plating solution formula in this stage is consistent with the formula in the first stage, and the current density is increased to 2ASD.
[0149] ③ In the third stage, a large-grain copper layer is grown on the copper-plated layer by adjusting the electroplating solution formula and current density. The formula for this stage is: CuSO4·5H2O concentration is 60g / L, H2SO4 concentration is 80g / L, glucose concentration is 18g / L, and ammonium molybdate concentration is 16g / L. The electroplating time is 15s, the current density is increased to 3ASD, and the temperature is heated to 45°C by a heating rod. Stirring is continued during the electroplating process.
[0150] ④The fourth stage uses a small current to deposit a thin copper layer to fix the large copper layer in the third step to prevent it from falling off. The formula of this stage is the same as the electroplating formula of the first stage. The refinement process is: electroplating time is 30s, current density is 0.2ASD, and temperature is 25℃.
[0151] The roughening process is as follows:
[0152] The surface copper layer is etched and roughened using the principle of chemical corrosion. The composite copper foil prepared in the first step is immersed in a roughening solution for 0.5 min. The roughening solution temperature is 40°C. The roughening solution formula is: hydrogen peroxide concentration is 130 ml / L; sulfuric acid solution concentration is 50 ml / L; chloride ion concentration is 10 ppm; copper ion concentration is 25 g / L.
[0153] The process of anti-oxidation treatment is:
[0154] The metal film after continuous electroplating is immersed in the prepared corrosion inhibition solution for 2 minutes, and the temperature of the corrosion inhibition solution is 45° C. The formula of this slow-release solution is: BTA concentration is 12 mg / L, and ammonium molybdate concentration is 15 mg / L.
[0155] Comparative Example 1
[0156] A composite current collector, the preparation process of which is as follows:
[0157] S1. Obtaining a surface metallized base film;
[0158] S2. electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0159] S3. The primary current collector is subjected to a roughening treatment, and then subjected to an anti-oxidation treatment to form an anti-oxidation layer to obtain a current collector.
[0160] The process of electroplating is:
[0161] The surface metallized film was thickened by conventional one-time electroplating process. The current density was 0.6ASD and the electroplating time was 7min. The plating solution formula was: CuSO4·5H2O concentration was 220g / L, H2SO4 concentration was 60g / L, and the inorganic additive was Cl - The concentration is 18 mg / L, the organic additives include thiazolidinethione at a concentration of 0.0015 g / L, poly(2,6-bis-propane sulfonate) at a concentration of 0.02 g / L, and PEG-6000 at a concentration of 0.05 g. The electroplating temperature is room temperature 25°C, and the plating solution is stirred continuously during the electroplating process to reduce concentration polarization.
[0162] The roughening process is as follows:
[0163] The surface copper layer is etched and roughened using the principle of chemical corrosion. The composite copper foil prepared in the first step is immersed in a roughening solution for 0.5 min. The roughening solution temperature is 40°C. The roughening solution formula is: hydrogen peroxide concentration is 130 ml / L; sulfuric acid solution concentration is 50 ml / L; chloride ion concentration is 10 ppm; copper ion concentration is 25 g / L.
[0164] The process of anti-oxidation treatment is:
[0165] The metal film after continuous electroplating is immersed in the prepared corrosion inhibition solution for 2 minutes, and the temperature of the corrosion inhibition solution is 45° C. The formula of this slow-release solution is: BTA concentration is 12 mg / L, and ammonium molybdate concentration is 15 mg / L.
[0166] Comparative Example 2
[0167] A composite current collector, the preparation process of which is as follows:
[0168] S1. Obtaining a surface metallized base film;
[0169] S2. electroplating the surface metallized base film to thicken the metal layer of the surface metallized base film to obtain a primary current collector;
[0170] S3. Performing an anti-oxidation treatment on the initial current collector to form an anti-oxidation layer to obtain a current collector.
[0171] The process of electroplating is:
[0172] The surface metallized film was thickened by conventional one-time electroplating process. The current density was 0.6ASD and the electroplating time was 5min. The plating solution formula was: CuSO4·5H2O concentration was 220g / L, H2SO4 concentration was 60g / L, and the inorganic additive was Cl - The concentration is 18 mg / L, the organic additives include thiazolidinethione at a concentration of 0.0015 g / L, poly(2,6-bis-propane sulfonate) at a concentration of 0.02 g / L, and PEG-6000 at a concentration of 0.05 g. The electroplating temperature is room temperature 25°C, and the plating solution is stirred continuously during the electroplating process to reduce concentration polarization.
[0173] The process of anti-oxidation treatment is:
[0174] The metal film after continuous electroplating is immersed in the prepared corrosion inhibition solution for 2 minutes, and the temperature of the corrosion inhibition solution is 45° C. The formula of this slow-release solution is: BTA concentration is 12 mg / L, and ammonium molybdate concentration is 15 mg / L.
[0175] The contact angle test was performed on the composite current collector provided in each embodiment and comparative example, and the negative electrode slurry (mainly graphite) was coated on the composite current collector, and rolled after drying to obtain a lithium battery negative electrode sheet. The peeling strength of the negative electrode slurry from the current collector surface was tested by a standard peeling test method; then the prepared negative electrode sheet was installed in the battery according to the lithium battery soft pack battery preparation process, and the battery cycle performance was measured by a national standard cycle test method;
[0176] The specific test method for peel strength is as follows:
[0177] Pole stripping: size 30mm×70mm,
[0178] Fixing method: The pressure-sensitive 3M-VHB double-sided tape is attached to the electrode surface, and the other side is attached to the stainless steel plate.
[0179] Test process: The stainless steel plate and the current collector are fixed on the two fixtures of the equipment, and then a 180-degree peel test is performed at a speed of 100 mm / min and a load of 10 N.
[0180] The specific cycle performance test method is:
[0181] At room temperature of 25℃, the battery was charged at 1C for 150 minutes at constant current and constant voltage, and discharged at constant current and constant voltage to 2.75V for one cycle. The number of cycles was 500.
[0182] The results are shown in the following table:
[0183]
[0184] It can be seen from Example 1 and Comparative Example 2 that, compared with single electroplating, the contact angle of the coating surface after multiple continuous electroplating decreased significantly, from 97.6° to 70.6°, and the hydrophobic surface was modified into a hydrophilic surface. The smaller the contact angle, the smaller the surface tension during the coating of the negative electrode slurry, the greater the bonding force, and the greater the peel strength. The greater the peel strength, the better the cycle performance of the final battery end. Although Comparative Example 1 uses a single electroplating + chemical roughening process to reduce the surface contact angle to a certain extent, its preparation process will be more complicated.
[0185] As can be seen from Example 1 and Example 2, after the same roughening treatment, different passivation solution formulas also have a very significant impact on the contact angle. The interface treated with the BTA+ammonium molybdate compound passivation solution formula has a smaller contact angle than the interface treated with the single BTA passivation solution. The applicant believes that the reason may be that the passivation film formed by the reaction of pure BTA with the copper surface has a large number of hydrophobic groups (benzene rings), resulting in a large interface contact angle, while in the BTA+ammonium molybdate compound passivation solution, a large number of hydrophobic groups (benzene rings) are replaced by hydrophilic groups (ammonium radicals), showing better wetting properties.
[0186] It can be seen from Example 1 and Example 3 that after the continuous multi-stage electroplating treatment, the chemical roughening process can be further reduced.
[0187] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A current collector, characterized in that: The current collector comprises a base film and a metal layer attached to the surface of the base film. The surface contact angle of the current collector is 60° to 80°, and the square resistance of the current collector is 2 to 200 mΩ / □.
2. The current collector according to claim 1, characterized in that: The base film material of the current collector includes at least one of polyethylene, biaxially oriented polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate and polypropylene; and / or The base film thickness of the current collector is 2 μm to 20 μm; and / or The thickness of the metal layer of the current collector is 0.1 μm to 10 μm.
3. A method for preparing a current collector according to any one of claims 1 to 2, characterized in that: The method comprises: A surface metallized base film is obtained; Electroplating the surface metallized base film to obtain a primary current collector; Performing an anti-oxidation treatment on the initial current collector to obtain a current collector; The electroplating process includes at least two stages of electroplating, and the last stage of electroplating in the electroplating process is a grain refinement strengthening stage of electroplating.
4. The method for preparing a current collector according to claim 3, characterized in that: The electroplating process in the grain refinement strengthening stage meets the following requirements: the electroplating time is 5s to 30s, the electroplating current density is 0.2ASD to 1ASD, and the electroplating temperature is 20°C to 30°C.
5. The method for preparing a current collector according to any one of claims 3 to 4, characterized in that: The electroplating process includes four stages of electroplating.
6. The method for preparing a current collector according to claim 5, characterized in that: The first electroplating stage of the four electroplating stages is current ramping stage electroplating, and the electroplating process of the current ramping stage meets the following requirements: electroplating time is 0.5min to 1min, electroplating current density is 0.2ASD to 1ASD, and electroplating temperature is 30°C to 50°C.
7. The method for preparing a current collector according to claim 5, characterized in that: The second electroplating stage of the four-stage electroplating is a stable continuous stage electroplating, and the process of the stable continuous stage electroplating meets the following requirements: the electroplating time is 1 min to 3 min, the electroplating current density is 1 ASD to 3 ASD, and the electroplating temperature is 20° C. to 50° C.
8. The method for preparing a current collector according to claim 5, characterized in that: The third electroplating stage of the four-stage electroplating is the electroplating in the grain coarsening stage, and the electroplating process in the grain coarsening stage meets the following requirements: the electroplating time is 10s to 20s, the electroplating current density is 2.5ASD to 3ASD, and the electroplating temperature is 50°C to 60°C.
9. The method for preparing a current collector according to any one of claims 3 to 4, characterized in that: The electroplating treatment includes: electroplating in the current ramping stage, electroplating in the stable continuous stage, electroplating in the grain coarsening stage and electroplating in the grain refinement strengthening stage; The components of the plating solution in the current ramping stage electroplating, the stable continuous stage electroplating and the fine grain strengthening stage electroplating satisfy any one of the following (A) to (F): (A) The mass concentration of CuSO4·5H2O is 100g / L~300g / L; (B) The mass concentration of H2SO4 is 20g / L to 90g / L; (C)Cl - The mass concentration is 10mg / L~100mg / L; (D) the mass concentration of tetrahydrothiazolidinethione is 0.0005 g / L to 0.001 g / L; (E) the mass concentration of sodium poly(2,6-bis(2,6-propane sulfonate)) is 0.01 g / L to 0.02 g / L; (F) the mass concentration of polyethylene glycol is 0.03 g / L to 0.05 g / L; Wherein, the components of the electroplating solution in the grain coarsening stage satisfy any one of the following (G) to (J): (G) The mass concentration of CuSO4·5H2O is 30 g / L to 100 g / L; (H) The mass concentration of H2SO4 is 20g / L~90g / L; (I) The mass concentration of glucose is 15 g / L to 25 g / L; (J) The mass concentration of ammonium molybdate is 10 g / L to 20 g / L.
10. The method for preparing a current collector according to claim 3, characterized in that: The anti-oxidation treatment comprises immersing the primary current collector in an anti-oxidation solution, wherein the anti-oxidation solution comprises a BTA corrosion inhibitor and ammonium molybdate.
11. The method for preparing a current collector according to claim 10, characterized in that: The mass concentration of the BTA corrosion inhibitor in the anti-oxidation solution is 5 mg / L to 60 mg / L; and / or The mass concentration of ammonium molybdate in the anti-oxidation liquid is 5 mg / L to 80 mg / L; and / or The soaking time is 2 to 5 minutes; and / or The soaking temperature is 30°C to 70°C.
12. A pole piece, characterized in that: The pole piece comprises the current collector according to any one of claims 1 to 2 or the current collector prepared by the method according to any one of claims 3 to 11.
13. A secondary battery, characterized in that: The secondary battery comprises the electrode sheet according to claim 12.
Citation Information
Patent Citations
Preparation method of negative electrode composite current collector and product prepared by preparation method
CN114678534A
Current collector and preparation method thereof, battery pole piece and battery
CN116137330A
Novel bipolar composite current collector and preparation process thereof
CN117423838A
Composite copper foil with spherical structure on surface
CN220856616U
Negative electrode plate, secondary battery and electric device
WO2024108436A1